Situation awareness in intensive care unit nurses: A qualitative directed content analysis - Ghaderi, Chiman; Esmaeili, Roghayeh; Ebadi, Abbas (Frontiers in Public Health, 2022)
Background: Situation awareness (SA) is an essential cognitive construct to create positive patient safety outcomes. SA of the nurses in the intensive care unit (ICU), where conditions may change rapidly, is particularly important. The present study aimed to explain the perception and experience of SA in ICU nurses based on Endsley's SA model. Materials and Methods: This qualitative directed content analysis was conducted on nurses in six hospitals in Tehran, Iran, from December 2020 to July 2021. Twenty-seven ICU nurses were selected using purposive sampling. Data were collected by semi-structured interviews and field observations. The data were analyzed based on the Elo and Kyngas method modified by Assaroudi et al.(2018). COREQ checklist was used to report the research. Results: The concept of SA in ICU nurses, based on Endsley's model, includes perception of patients' clinical cues, perception of the human environment, perception of the physical environment, and perception of the organizational environment as generic categories of the perception of the elements in the environment. SA in ICU nurses also includes the main categories of comprehension the current situation through a sense of salience and interpretation of cues and projection the future situation through the prediction of patient status into the near future and environmental foresight. Conclusion: Findings have further developed the concept of SA in ICU nurses based on Endsley's SA model. The insights and knowledge gained from this study can be useful for future practice, education, and research on SA among ICU nurses.